Xylanase Supplementation and Performance of Broiler Chicken Fed Low Energy Diet - Govil, Kumar; Nayak, Sunil; Baghel, R.P.S.; Khare, A.; Patil, A.K.; Malapure, C.D.; Nayak, Anju (Indian Journal of Animal Nutrition, 2018)
This experiment was designed to evaluate the effects of xylanase supplementation on performance, nutrient digestibility and carcass traits of broilers. Seventy five day old chicks were randomly divided into 3 treatments, each treatment consisted of five replicates with 5 chicks in each replicate. Broilers were fed with standard diet to meet the nutrient requirements. There were 3 dietary treatments. T1 was standard broiler diet (positive control) without enzyme supplementation. T2 was same as T1 except in this diet energy was reduced by 100 kcal ME/kg diet (negative control). T3 was same as T2 except that it was supplemented with enzyme xylanase (@100 g/tonne). Significantly (P<0.05) higher average weight (2553.80±67.47 g), better feed efficiency (0.541±0.006) and performance index (1382.40±54.07) were observed in broilers fed T3 diet. Feed intake was similar in all the treatments. The retention of protein improved (P<0.05) due to supplementation of xylanase enzyme. Supplementation of xylanase in negative control diet increased (P<0.05) the dressed, eviscerated and drawn weight of broilers. Therefore, low energy diet supplemented with xylanase @ 100 g/ tonne improved growth, nutrient utilization and carcass characteristics in broilers.